Desempenho da filtração híbrida na coleta de nanopartículas, calcário dolomítico e pó de sinterização de uma indústria siderúrgica - Castro, Bruno José Chiaramonte de (Universidade Federal de São Carlos, 2022)
A promising alternative for air pollution control by industries is the replacement of conventional equipment, such as electrostatic precipitators and bag filters, by hybrid filters, which combine the phenomena of electrostatic precipitation and fabric filtration. Hybrid filtration has been studied in the three last decades and good results have been reported, in relation to superfine particulate matter collection efficiency, to the operation at low pressure drops and high surface filtration velocities. However, most of the works evaluated the application of hybrid filters to the pollution control in coal fired power plants. Until now, no study has been reported to the application in the steel industry. Furthermore, very little is still known about hybrid filtration of nanoparticles, which are extremely dangerous to the human health. Thus, this work aimed to evaluate the hybrid filtration of nanoparticles and of microparticles from the sinter process of a steel industry. The experimental test to evaluate the hybrid filtration of nanoparticles followed a factorial design 2^3, with the factors surface filtration velocity (1.0 and 2.0 m/min), electric field intensity (0.0 and 4.0 kV/cm) and filter medium (polyacrylonitrile and polyacrylonitrile with polytetrafluorethylene membrane). The results showed that, with the application of electric voltage, the nanoparticles which passed through the electrostatic precipitator without been collected had their collection intensified in the filter, due to the electrostatic attraction mechanism. Increases greater than 10.0 % in the polyacrylonitrile filter quality factor were obtained with the application of electric voltage in the electrostatic precipitator. To study the hybrid filtration applied to the steel industry, experimental tests were performed at a surface filtration velocity of 2.0 m/min, electric field intensities of 0.0, 4.0 and 5.0 kV/cm, and with a polyester filter. Two particulate matters were used for comparison: dolomitic limestone and sinter dust. With both dusts, the pressure drop increased slowly when electric voltage was applied, due to the particle collection in the electrostatic precipitator, increasing the total filtration time. With the sinter dust, the increase in the electric voltage caused only the finest particles to reach the polyester filter. However, no reduction in cake porosity was observed. For the industrial application, the results point that the bag cleaning frequency of a hybrid filter can be reduced in comparison to that of a conventional bag filter, which can lead to the increase in the bag lifetime and, consequently, to the reduction of maintenance costs.
Performance of hybrid filtration in the collection of nanoparticles, dolomitic limestone and sinter dust from a steel industry
Keywords: Filtro híbrido; Eficiência de filtração; Filtração de gases; Material particulado; Partículas nanométricas; Hybrid filter; Filtration efficiency; Gas filtration; Particulate matter; Nanoparticles; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA